The light of Florence Nightingale in the care for COVID-19 patients in primary health care - Maria de las Mercedes de Dios-Aguado; Sagrario Gómez-Cantarino; Paulo Joaquim Pina Queirós; Maria Angélica de Almeida Peres (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To analyze the contributions of Florence Nightingale`s care model in the COVID- 19 pandemic. Method Reflection that addresses her theoretical model and its validity in this pandemic, using interpretative research methods and limiting nursing care to primary care. Results Some pandemics that have caused great impact in humanity are reviewed throughout history; the evolution of nursing care in relation to pandemics is studied; the genesis of community nursing is considered, and Nightingale's care model is reviewed in COVID-19. Conclusions Florence Nightingale's thinking withstands the passage of time and, today, as the COVID-19 pandemic rages across the planet, her concept of holistic care and her idea of the art of nursing take on special significance by considering the context involving patients, families and communities.